Acute hypotension induced by suction of cystic fluid containing extremely high concentrations of catecholamines during resection of giant pheochromocytoma. Issue 4 (2nd June 2019) - Samejima, Mio; Taguchi, Satoru; Miyagawa, Shogo; Matsumoto, Ryuki; Omura, Shota; Ninomiya, Naoki; Nakamura, Yu; Yamaguchi, Tsuyoshi; Kinjo, Manami; Tambo, Mitsuhiro; Okegawa, Takatsugu; Koba, Tsuyuha; et al.
Abstract : Introduction: Since pheochromocytomas present with various complications due to catecholamine hypersecretion, their perioperative management needs special attention. Case presentation: A 45‐year‐old man visited our hospital with a complaint of abdominal swelling. Radiological and endocrinological assessments determined the tumor as a giant (>20 cm) cystic pheochromocytoma. After administration of doxazosin, the patient underwent radical surgery. Since the tumor was extremely large and fixed to surrounding structures, we punctured it and aspirated cystic fluid to improve the tumor's mobility. However, during the aspiration, the patient developed acute hypotension, which could be reversed by suction withdrawal and vasopressor administration. A similar event occurred during a second aspiration. Eventually, the tumor was successfully excised with negative surgical margin. The cystic fluid proved to contain extremely high concentrations of catecholamines, which might result in the hypotension. Conclusion: We report the first case who developed acute hypotension due to aspiration of cystic fluid from giant pheochromocytoma.